2009
DOI: 10.1179/174313208x346134
|View full text |Cite
|
Sign up to set email alerts
|

Effects of colchicine on strength–duration properties of sensory and motor axons

Abstract: The lack of any effect on the SDTC by colchicine might have been due to the fact that axonal degeneration caused by colchicine affects the Na(+)-K(+) ATP pump or that it affects internodal channels other than nodal channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…We show no significant difference in corneal sensation or corneal nerve morphology between patients treated with or without colchicine. This is supported by a study of 29 patients with BD which also reported no difference in neurophysiology between patients treated with or without colchicine ( 50 ).…”
Section: Discussionmentioning
confidence: 54%
“…We show no significant difference in corneal sensation or corneal nerve morphology between patients treated with or without colchicine. This is supported by a study of 29 patients with BD which also reported no difference in neurophysiology between patients treated with or without colchicine ( 50 ).…”
Section: Discussionmentioning
confidence: 54%